Structural, surface morphology and radiation shielding properties of barium ferrite powder. (3rd June 2021) - Ali, Atif Mossad; Issa, Shams A M; Algarni, H; Tekin, H O; Zakaly, Hesham M H; Sayed, M A; Rashad, M
Abstract: In this study, Barium ferrite (BaFe12 O19 ) was prepared in powder form using the sol-gel method. Next, structural, surface morphology, and radiation shielding properties of Barium ferrite compound were determined using experimental and simulation methods. The structural and surface morphology were characterised using x-ray diffraction (XRD) and the scanning electron microscope (SEM). The formation of hexagonal structure has been verified by XRD patterns for synthesised pure BaFe12 O19 . The amplitude of XRD peaks declines as the FWHM rises, indicating that crystallinity has degraded and crystallite size has decreased. SEM images provide accurate representations of surfaces. The topography of the surface is characterized by the presence of several spherical granules. Additionally, the mean diameter of the spherical granules was determined to be approximately 30 nm using the histogram. Moreover, FLUKA simulation code was used to calculate some radiation shielding parameters such as linear attenuation coefficients (4.639, 0.554, 0.336 and 0.2013 cm −1 ), mass attenuation coefficients (0.8787, 0.1049, 0.0686 and 0.0381 cm 2 g −1 ), half value layers (0.1494, 1.2512, 2.0629 and 3.4434 cm) and mean free path values (0.21554, 1.8051, 2.9762and 4.9677 cm) against 0.81, 0.356, 0.911 and 2.614 MeV photon energies, respectively. The results showed that synthesized Barium ferrite has good surface renditions and distinguished spherical granules along with promising gamma-ray attenuation properties.